Cover. Issue 3 (12th March 2019) - Mori, Gentaro; Oda, Yukari; Sakamoto, Kei; Ito, Taichi; Yajima, Yasutomo
Abstract : The cover image is based on the Original Research Clinical evaluation of full‐arch screw‐retained implant‐supported fixed prostheses and full‐arch telescopic‐retained implant‐supported fixed prostheses: A 5–12 year follow‐up retrospective study by Gentaro Mori et al., DOI:10.1111/clr.13406 .